All-optical structuring of laser-driven proton beam profiles - Lieselotte Obst-Huebl (Nature Portfolio, 2018)
Shaping particle beams generated from laser-plasma accelerators is challenging. Here the authors demonstrate an all-optical method to structure the accelerated proton beam by modulating and imprinting the spatial laser profile onto the proton beam.